Эффективность линейных импульсных электромеханических преобразователей, предназначенных для создания ударных нагрузок и высоких скоростей - Болюх, В.Ф.; Олексенко, С.В.; Щукин, И.С. (Електротехніка і електромеханіка, 2015)
Разработаны компьютерные модели линейных импульсных электромеханических преобразователей коаксиальной
конфигурации с ферромагнитным сердечником. Проведен выбор параметров индукционно-динамического, электродинамического и электромагнитного преобразователей, обеспечивающих максимальные ударные нагрузки и скорости.
Проведен сравнительный анализ эффективности данных преобразователей с помощью интегрального показателя.
Показано, что индукционно-динамический преобразователь не является лучшим ни по одной из стратегий выбора.
Электромагнитный преобразователь является наиболее эффективным для силового воздействия, а электродинамический преобразователь – для обеспечения наибольшей скорости. Розроблені комп’ютерні моделі лінійних імпульсних електромеханічних перетворювачів коаксіальної конфігурації з
феромагнітним осердям. Виконано вибір параметрів індукційно-динамічного, електродинамічного та електромеханічного перетворювачів, що забезпечують максимальні ударні навантаження та швидкості. Проведений порівняльний
аналіз ефективності зазначених перетворювачів за допомогою інтегрального показника. Показано, що індукційнодинамічний перетворювач не є найкращим ні за якою стратегією вибору. Електромагнітний перетворювач є найбільш ефективнішим для силової дії, а електродинамічний перетворювач – для забезпечення найбільшої швидкості. Considered linear impulse electromechanical converters (LIEC)
are used to create a significant impact and high-acceleration
actuators on a short active site. The most effective types of LIEC
are induction-dynamic (IDC), electro-dynamic (EDC) and electro-magnetic (EMC) converters. In all these types of short-term
excitement LIEC carried briefly of the inductor from a pulsed
source. This occurs when the magnetic field of the inductor causes
the electro-dynamic or electromagnetic forces, leading to a linear
movement of the armature. However, the issue at evaluating the
effects of IDC, EDC and EMC, for creating a shock simultaneously with high speed to the specified criteria in the presence of
ferromagnetic core virtually unexplored. The paper presents the
simulated computer-WIDE 2D model of LIEC of coaxial configuration with ferromagnetic core by using software package
COMSOL Multiphysics 4.4, taking into account the related electro-magnetic, thermal, and magnetic fields. In addition a synthesis
of high-performance IDC, EDC and EMC to ensure maximum
impact and speed of the operating element, whereby the comparative analysis of the effectiveness of the IDC, EDC and EMC via an
integral index, taking into account the maximum value and momentum of electro-dynamic or electromagnetic force acting on the
armature, maximum and average speed armature, efficiency, mass
and dimensions performance transducer stray field, the maximum
current density in the inductor is carried out. On the basis of the
eight selection policies set the most efficient types of power and
speed LIEC. It is shown that any one of the strategies IDC selection is not the best. To ensure maximum impact force is the most
effective EMC and to ensure the greatest speed – EDC.